Surgical Pathology of Lung Cancer - Rezaei, M. Katayoon; Nolan, Norris J.; Schwartz, Arnold M. (Seminars in Respiratory and Critical Care Medicine, 2013)
The diagnosis, treatment, and management of lung tumors represent a complex set of decision algorithms and require the cooperation and interaction of a team of experts and support systems. The surgical pathologist, an early, important member of the diagnostic team, uses clinical and radiological evidence to differentiate benign from malignant tumors and renders a unique diagnosis that provides both prognostic and treatment information. Using routine histopathologic criteria, histochemical and immunohistochemical stains, and molecular and genetic testing, surgical pathologists and cytopathologists may distinguish between small cell and other bronchogenic carcinomas, separate adenocarcinomas from squamous cell carcinomas, differentiate between pleural carcinomas and diffuse malignant mesotheliomas, and discriminate among the varieties of neuroendocrine carcinomas. Among adenocarcinomas, the pathological examination stratifies those tumors with absent or minimal central invasive cores that have an excellent prognosis from the more common adenocarcinomas with larger invasive components. These distinctions are necessary based on differences in tumor biology, response to therapy, and prognosis for these different histological types. Histopathologic analysis should attempt to provide a precise diagnosis and limit the usage of the term non–small cell carcinoma. The team approach also enables the optimal use of tumor tissue for diagnostic purposes as well as molecular genetic testing and the discovery of targetable sites for therapeutic management. Though low-stage tumors tend to be initially treated with surgical resection, more advanced stages will be approached with limited tissue acquisition, necessitating a strategy for best practices of scarce tissue resources. The awareness of diagnostic modalities and tissue handling by all members of the team ensures the best patient-centered care.
Keywords: lung cancer; adenocarcinoma; squamous cell carcinoma; small cell carcinoma; large cell carcinoma; neuroendocrine carcinoma; adenoid cystic carcinoma; mucoepidermoid carcinoma; mesothelioma